Modeling the Psychological Process of Retail Vendors on QR-Code Payment Adoption in Nepal - Tamang, Govinda; Aryal, Abhinav (International Journal of Operational Research/Nepal, 2024)
The purpose of this study is to examine the psychological process of retail vendors while adopting QR-code payment system in Nepal. By using behavioral reasoning theory (BRT) as the theoretical model, this study hypothesizes relationships between values, reasons constructs, attitude, and intention towards QR-code payment adoption among Nepalese retail vendors. The hypothesized relationships have been assessed by collecting 300 samples and applying partial least squares structural equation modeling (PLS-SEM) to analyze the data. The finding of this study is congruent with the main premise of BRT which states that reasons serve as important linkages between people’s values, their attitude, and their intention. The study shows reasons for adoption (convenience, speed, simplicity) account for most of the variance in attitude towards adoption of QR-code payment. However, the findings show no direct linkages between the reasons constructs and the intention to adopt QR-code payment. The finding of this study stresses the importance for marketers to continue providing benefits that form the reasons for adoption of QR-code payment for the vendors to ensure continued adoption.